Answer: C) 1
==============================================================
Work Shown:
I'm assuming you meant to write
where all of the "x+4" is the exponent.
If we shift f(x) 5 units to the right to end up with g(x), then,
![g(x) = f(x-5)\\\\g(x) = 2^(x-5+4)\\\\g(x) = 2^(x-1)\\\\](https://img.qammunity.org/2022/formulas/mathematics/college/yegpbnw5x7y1pdw904xh0d16fhchgrmni5.png)
In the second step, I replaced every copy of x with x-5 so that I could apply the translation of 5 units to the right.
The exponent for g(x) is x-1, which matches up with x-k. We see that k = 1.